Hepatic Radioembolization as a Bridge to Liver Surgery - Braat, Arthur J. A. T.; Huijbregts, Julia E.; Molenaar, I. Quintus; Borel Rinkes, Inne H. M.; van den Bosch, Maurice A. A. J.; Lam, Marnix G. E. H. (Frontiers in Oncology, 2014)
Treatment of oncologic disease has improved significantly in the last decades and in the future a vast majority of cancer types will continue to increase worldwide. As a result, many patients are confronted with primary liver cancers or metastatic liver disease. Surgery in liver malignancies has steeply improved and curative resections are applicable in wider settings, leading to a prolonged survival. Simultaneously, radiofrequency ablation (RFA) and liver transplantation (LTx) have been applied more commonly in oncologic settings with improving results. To minimize adverse events in treatments of liver malignancies, locoregional minimal invasive treatments have made their appearance in this field, in which radioembolization (RE) has shown promising results in recent years with few adverse events and high response rates. We discuss several other applications of RE for oncologic patients, other than its use in the palliative setting, whether or not combined with other treatments. This review is focused on the role of RE in acquiring patient eligibility for radical treatments, like surgery, RFA, and LTx. Inducing significant tumor reduction can downstage patients for resection or, through attaining stable disease, patients can stay on the LTx waiting list. Hereby, RE could make a difference between curative of palliative intent in oncologic patient management. Prior to surgery, the future remnant liver volume might be inadequate in some patients. In these patients, forming an adequate liver reserve through RE leads to prolonged survival without risking post-operative liver failure and minimizing tumor progression while inducing hypertrophy. In order to optimize results, developments in procedures surrounding RE are equally important. Predicting the remaining liver function after radical treatment and finding the right balance between maximum tumor irradiation and minimizing the chance of inducing radiation-related complications are still challenges.